Social, Emotional, and Spiritual Behavior of Madrasah Aliyah Adolescents: a Qualitative Analysis of Student Characteristics - Fellia, Annida Fitri; Ediat, Ediat; Sholihah, Tria Maratus; Rois, M. Jahdan (Gunung Djati Conference Series, 2026)
This study aims to identify: the forms of social behavior demonstrated by Madrasah Aliyah adolescents in their interactions within and outside the school environment; the level of emotional intelligence reflected in how they manage feelings, cope with pressure, and build relationships with others; the spiritual behavior of Madrasah Aliyah adolescents as seen in their religious practices and the moral values they uphold; and the factors influencing the development of their social, emotional, and spiritual behavior, viewed from both individual and environmental characteristics. This study employs a descriptive qualitative approach to understand the social, emotional, and spiritual behavior of Madrasah Aliyah adolescents through interviews, observations, and documentation. Primary data were collected from students as well as counseling and Islamic education teachers, while secondary data were obtained from school documents and relevant literature. Data were analyzed using the Miles and Huberman model, data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation to maintain accuracy and credibility. The findings indicate that the social, emotional, and spiritual behavior of Madrasah Aliyah adolescents is influenced by their religious environment, family background, peer groups, and digital media. At school, they tend to display prosocial behavior, cooperation, and deliberation, while outside school they are more selective in choosing peer groups. Their emotional development is reflected in their growing self-awareness and self-regulation, although some still avoid confrontation. Their spiritual values play a significant role in emotional regulation and identity formation, although the consistency of their religious practices varies between school and home.